Digital Services as an Approach to Enhancing Transparency and Achieving Sustainability in Local Governance: A Field Study of a Selected Sample of Libyan Municipalities (Derna Academy Journal for Applied Sciences, 2025)
This study aimed to determine the role of digital services as an input for enhancing transparency and achieving sustainability in local governance, through a field study conducted on a selected sample of Libyan municipalities.The study adopted the descriptive analytical approach and used a questionnaire as the primary data collection tool from a sample of (598) individuals. The questionnaire consisted of (40) items distributed across three main variables: the independent variable (Digital Services and Enhancing Transparency), the dependent variable (Achieving Sustainability in Local Governance), and the Challenges variable.Descriptive statistics results showed that the level of implementing digital services in enhancing transparency was low, with a general mean of (1.76) and a relative weight of (35.2%). Furthermore, the level of achieving sustainability was moderate tending toward low, with a general mean of (2.05) and a relative weight of (41.1%). Results also revealed the presence of significant challenges and obstacles to digital transformation, with a very high mean of (4.17) and a relative significance of (83.4%). The findings confirmed a very strong positive correlation with statistical significance between the level of implementing digital services and the level of transparency in local governance. They also showed a medium-strength positive correlation with statistical significance between digital services and enhancing sustainability across its components (environmental, economic, and social). The results further emphasize that technical, organizational, and human barriers constitute negative factors that limit the effectiveness of digital services in promoting transparency and achieving sustainability.